"It's not like family, it is family": Reflections on a mentoring program for boys of color. (October 2019) - Durand, Tina M.
Early adolescence is a time of great potential and vulnerability, especially for boys of color. Research is replete with examples of how mentoring can help young people through this challenging period, but less is known about what students themselves want from such relationships. Tina Durand interviewed and conducted focus groups with boys of color participating in an after-school mentoring program to learn what they valued in a mentor. Common themes included mentors' ability to relate to students; their unconditional support; their affirmation of students' best traits, especially in the face of racial stereotypes; and their ability to inspire students .